Grain-size distribution characteristics of sediments in coastal shallow waters from Van Don to Tien Yen - Ha Coi, Northwest Gulf of Tonkin, Vietnam, according to End-member modelling analysis - Le, Duc Anh; Mai, Duc Dong; Tran, Thi Thuy Huong; Le, Duc Luong; Nguyen, Nhu Trung; Vu, Hai Dang; Bui, Van Nam; Pham, Thu Hien; Duong, Van Hao; Nguyen, Anh Minh (Vietnam Journal of Marine Science and Technology, 2024)
The study involved the collection of eighteen surface sediment samples from the coastal shallow water area from Van Don to Tien Yen - Ha Coi in the Northwestern section of the Gulf of Tonkin to analyze their particle size composition. Utilizing the EMMAgeo end-member analysis model, four characteristic particle sizes (4EM) of 0.34, 7.7, 130, and 230 µm, corresponding to clay, fine silt, and fine sand of varying sizes were identified. In conjunction with the sedimentary environment, the spatial distribution analysis of these end members allowed a detailed determination of the formation conditions and distribution of the sediment components. Clay deposits (EM1) are primarily intercalated between the islands. At the same time, fine silt (EM2) is concentrated in the northern part of the study area, transported by flows, and deposited in a low-energy environment. Fine sand sediments (EM3 and EM4) are distributed along the coast of the Van Don peninsula in the Southern part of the study area and likely formed in association with tidal-wave processes under higher energy conditions compared to the North.